2021
DOI: 10.1002/hep.32112
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte‐specific deletion of adipose triglyceride lipase (adipose triglyceride lipase/patatin‐like phospholipase domain containing 2) ameliorates dietary induced steatohepatitis in mice

Abstract: Background and Aims Increased fatty acid (FA) flux from adipose tissue to the liver contributes to the development of NAFLD. Because free FAs are key lipotoxic triggers accelerating disease progression, inhibiting adipose triglyceride lipase (ATGL)/patatin‐like phospholipase domain containing 2 (PNPLA2), the main enzyme driving lipolysis, may attenuate steatohepatitis. Approach and Results Hepatocyte‐specific ATGL knockout (ATGL LKO) mice were challenged with methionine‐choline–deficient (MCD) or high‐fat high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…77,78 Previous studies showed that liver-specific ATGL deficiency improved glucose tolerance by increasing hepatic glucose utilisation and reducing hepatic glucose output without reducing hepatic steatosis. 79,80 However, the use of atglistatin, a chemical inhibitor of ATGL, in mice fed a high-fat diet reduced adipose tissue lipolysis, leading to a reduction in FA flux from the adipose tissue to the liver. 81 This was accompanied by a decrease in liver steatosis due to reduced expression of the genes involved in lipid uptake, storage, and de novo lipogenesis.…”
Section: Lipid Droplet Lipolysis and Autophagymentioning
confidence: 99%
“…77,78 Previous studies showed that liver-specific ATGL deficiency improved glucose tolerance by increasing hepatic glucose utilisation and reducing hepatic glucose output without reducing hepatic steatosis. 79,80 However, the use of atglistatin, a chemical inhibitor of ATGL, in mice fed a high-fat diet reduced adipose tissue lipolysis, leading to a reduction in FA flux from the adipose tissue to the liver. 81 This was accompanied by a decrease in liver steatosis due to reduced expression of the genes involved in lipid uptake, storage, and de novo lipogenesis.…”
Section: Lipid Droplet Lipolysis and Autophagymentioning
confidence: 99%
“…Studies found that ATGL encoded by the patatin-like phospholipase domain-containing protein 2 (PNPLA2) gene may participate in NAFLD, of which ATGL knockout leads to LDs accumulation, while overexpression of ATGL could alleviate hepatic steatosis and increase FAs oxidation [53,54]. Recent study identified that despite enhancing hepatic steatosis, ATGL/PNPLA2 deficiency may decrease hepatic lipolysis and increase PPARδ, which protects hepatocyte from inflammation and ER stress [55]. HSL was considered a rate-limiting enzyme for TG hydrolysis.…”
Section: Lipolysismentioning
confidence: 99%
“…138 Furthermore, in in vitro models of inflammation induced in HepG2 hepatic cells by fatty acids and lipopolysaccharides (LPS), the effects of ATGL knockdown and PPARδ activation were protective against inflammation. 138 In addition, ATGL deficiency in the liver alleviated ER stress in MCD-and HFHC-diet-fed mice, as was shown by the lower protein levels of PERK and IRE1α and the reduced mRNA levels of Grp78. 138…”
Section: Lipotoxicity and Er Stressmentioning
confidence: 99%